Pengaruh Penggunaan Metode Aktif Debat Terhadap Critical Thinking Siswa dalam Pembelajaran Sejarah - Putri, Dhea Mardalia; Hastuti, Hera (Jurusan Sejarah FIS UNP, 2025)
This study aims to analyze the effect of implementing the active debate method on students’ critical thinking skills in history learning for grade X at SMK N 4 Padang. The background of this study is the los level of students’ critical thinking skills in understading historical material, caused by less interactive teaching methods. The active debate method was chosen because it is considered capable of stimulating students to analyze historical events from various perspectives. This research uses an experimental method with a Posttest-Only Control Group Design. The sample consisted of class X Animasi A as the experimental group and class X Desain Batik Kriya dan Tekstil as the Control Group, selected through cluster random sampling technique. Data were collected through a 20-item multiple-choice post-test and analyzed using normality tests, homogenety tests, and independent sample t-test with the help of IBM SPSS STATISTIC software. The results showed that the average post-test score of the experimental class was 69.00 and the control class was 75.33. The Hypothesis test significance improvementi in students critical thinking skill after implementing the active debate method. These findings indicate that the effectiveness of the active debate method needs to be suppoerted by other factors such as learning duration, student readiness, and material suitablity. Nevertheless, observation of the debate process shows the potential of this method in training students analysis and argumentation skills.